Comparative Evaluation of Microleakage Under APC Plus, APC Flash-Free and Conventional Stainless Steel Brackets: An In Vitro Study. Issue 4 (October 2022) - Majji, Somasekhar; Peddu, Revathi; Kalyani, M.; Devikanth,; Dokku, Aruna; Nuvusetty, Bhargavi
Aim: The aim of the study was to compare and evaluate the microleakage under the Adhesive Precoated Plus (APCP), APC Flash-Free (APCF), and conventional stainless steel (SLS) brackets on the occlusal and gingival sides of the bracket base. Materials and Methods: 66 extracted premolar teeth were collected and divided equally into 3 groups. Bonding was done with APCP, APCF, and conventional SLS brackets using Transbond XT. After bonding, the samples were stored in a distilled water and thermocycled for 3000 cycles, followed by immersion in a 2% methylene blue for 24 h. After cleaning, the teeth were mounted in acrylic and sectioned longitudinally at about the center of the bracket in a buccolingual direction. Microleakage was recorded using a stereomicroscope. Results: Kruskal–Wallis H test showed a significant difference ( P < .005) in the microleakage scores between the 3 groups. Mann–Whitney U test showed a significant difference between group 1 to group 2 and group 1 to group 3 ( P < .005) and an insignificant difference between group 2 and group 3 on the occlusal side ( P = .116) and on the gingival side ( P = .063). Conclusion: Conventional SLS bracket group exhibited greater microleakage scores at both occlusal and gingival sides, when compared with APCP and APCF groups.